Pharmacovigilance in Africa - Dodoo, A.N.; Ampadu, H.H. (Mann's Pharmacovigilance: Third Edition, 2014)
The last 20 years have seen seismic shifts in the political, civil, and healthcare environment in Africa. Currently, 33 national pharmacovigilance (PV) centers in Africa are full members of the WHO Programme for International Drug Monitoring, whilst another six are associate members. A recent analysis showed that the challenges facing African PV centers include the lack of human and financial resources. The total number of spontaneous reports from African countries is extremely low even for drugs that are used heavily within the region. Despite this low reporting, a safety signal - that is, extrapyramidal reactions with the antimalarial drug combination of amodiaquine + artesunate - has been generated entirely due to PV efforts in Africa. PV in Africa is evolving, and key stakeholders like the pharmaceutical industry are being brought on board. Indicators for PV exist (Strengthening Pharmaceutical Systems (SPS) Program, 2009) or are being developed. © 2014 by John Wiley & Sons, Ltd. All rights reserved.
Keywords: Adverse drug reactions (ADRs); Africa; Pharmacovigilance (PV); Strengthening PharmacovigilanceSystems (SPS) Program